2018
DOI: 10.1002/aoc.4756
|View full text |Cite
|
Sign up to set email alerts
|

Biological and catalytic evaluation of Ru(II)‐p‐cymene complexes of Schiff base ligands: Impact of ligand appended moiety on photo‐induced DNA and protein cleavage, cytotoxicity and C‐H activation

Abstract: Two organometallic Ru(II)‐p‐cymene complexes of the type [Ru(η6‐p‐cymene)(L)Cl]PF6 1 and 2, where L is N,N‐bis(4‐isopropylbenzylidene)ethane‐1,2‐diamine (bien, L1) or N,N‐bis (pyren‐2‐ylmethylene)ethane‐1,2‐diamine (bpen, L2) have been prepared and characterized well. Because of appended pyrenyl groups in coordinated bpen ligand, the complex 2 exhibits higher DNA and protein binding than complex 1 in which isopropylbenzyl groups are incorporated. Interestingly, the luminescent characteristic complex 2 is uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 66 publications
1
8
1
Order By: Relevance
“…Schiff bases are considered “exclusive ligands” because they play a key role in the development of coordination chemistry. Schiff base ligands are prepared easily and can be readily modified, both electronically and sterically . Schiff base ligands contain multiple potential donor sites, which allow them to bind metal ions with diverse coordination geometries such as bidentate and tridentate .…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases are considered “exclusive ligands” because they play a key role in the development of coordination chemistry. Schiff base ligands are prepared easily and can be readily modified, both electronically and sterically . Schiff base ligands contain multiple potential donor sites, which allow them to bind metal ions with diverse coordination geometries such as bidentate and tridentate .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, to induce cytotoxicity, the Ru complexes must be taken up by the cells. Recent research has shown that ligand hydrophobicity confers increased lipophilicity, which promotes the penetration of complexes through the cell membrane, resulting in cytotoxicity. The p -cymene ring and the appended benzyl group of the B-6GD ligand are expected to increase the permeability of Ru­(B-6GD) across the hydrophobic lipid bilayer of the cell membrane when compared to Ru ( 6G ). However, it has not been experimentally observed.…”
Section: Resultsmentioning
confidence: 99%
“…Paper NJC These complexes could act as a photosensitizer when exposed to light with a wavelength in their absorption range, allowing them to attain the excited triplet state via efficient intersystem crossing from the singlet excited state. 47 The triplet state can then activate molecular oxygen, converting it from a stable triplet ( 3 O 2 ) to a reactive singlet ( 1 O 2 ) for nucleic acid degradation. In a different scenario, the excited state complex could involve direct proton or electron transfer to the surrounding base pairs, resulting in the production of reactive radicals for cleavage processes.…”
Section: Complexesmentioning
confidence: 99%